Developing the Mali Disaster Risk Management Maproom - Dinku, Tufa; Faniriantsoa, Rija; Dinh, Dannie (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the development of the Mali Disaster Risk Management (DRM) Maproom, a collaborative effort between the International Research Institute for Climate and Society (IRI) and Mali’s National Meteorological Agency (Mali-Météo). Utilizing the ENACTS approach, which integrates limited observed data with satellite information to improve climate data quality, the DRM Maproom offers historical climate analysis, Standardized Precipitation Index (SPI) monitoring, and real-time seasonal updates. Designed to support disaster risk management, the tool enables government agencies, humanitarian organizations, and planners to anticipate climate-related disasters, improve early warning systems, and strengthen climate resilience across Mali.